6th Dubrovnik conference on sustainable development of energy water and environment systems - Todorović, Jovan (Journal of Applied Engineering Science, 2011)
The Conference on Sustainable Development of Energy, Water and Environment Systems (SDEWES), was held for its 6th consecutive time, on September 25 - 29, 2011 in Dubrovnik in Croatia.